“Don’t Vax Up”: The Real-Time Failure of Public STEM Education in the COVID-19 Era - Wolfmeyer, Mark; Lupinacci, John (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2022)
Although many other factors come to bear on present issues in the contemporary world, vaccine hesitancy and refusal are also the direct result of poor STEM education. In this article we employ a sociological thought experiment methodology to articulate the shortcomings of STEM education and suggest pathways for much needed changes in solving future pandemics and other 21st century challenges. The problems we expose in STEM education include unequal access to high quality education via inter and intra school tracking and curricular issues where STEM does not integrate with other disciplines, like social studies, and fails to engage a critical perspective on STEM informed by advanced philosophies of science and epistemology.